2014
DOI: 10.1186/1477-7525-12-21
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of injured patient and general population valuations of EQ-5D health states for New Zealand

Abstract: BackgroundA near-universal finding internationally is that patient valuations of their own health, represented using the EQ-5D system, are mostly higher than general population valuations of the same EQ-5D states. This paper investigates whether this result also applies to New Zealand. Despite the EQ-5D’s widespread use for cost-utility analysis in New Zealand, in particular by the Pharmaceutical Management Agency (PHARMAC) for health technology assessments, no previous studies comparing patient and general po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…Thirty per cent of eligible patients who were invited to join the study participated, and some selection bias may have occurred if those choosing to participate had higher or lower pre-injury HRQoL than those not participating. Follow-up rates were higher than or comparable to similar studies [16, 50, 5255] but lower than opt-out registry-based cohort studies [56]. There was evidence of some response bias (online Table 2); in particular, young, single males were less likely to return follow-up questionnaires as were those reporting more problems with alcohol and drugs, higher pain scores, poorer social functioning and less social support.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Thirty per cent of eligible patients who were invited to join the study participated, and some selection bias may have occurred if those choosing to participate had higher or lower pre-injury HRQoL than those not participating. Follow-up rates were higher than or comparable to similar studies [16, 50, 5255] but lower than opt-out registry-based cohort studies [56]. There was evidence of some response bias (online Table 2); in particular, young, single males were less likely to return follow-up questionnaires as were those reporting more problems with alcohol and drugs, higher pain scores, poorer social functioning and less social support.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies show retrospectively reported pre-injury HRQoL amongst injured populations is likely to show a small upward bias [38, 39, 52], for a variety of reasons [38, 39, 52, 57]. It is possible that some of the reduction in EQ-5D in our study arose from overestimation of pre-injury EQ-5D.…”
Section: Discussionmentioning
confidence: 74%
“…For many measures, participants were asked about their status before their sentinel injury, as well as at 3, 5, 12 and 24 months afterwards,13 allowing adjustment for pre-sentinel injury status. Validated outcome measures include WHO Disability Assessment Schedule (WHODAS; disability),47 Kessler-6 (psychological distress)48 and the EQ-5D (general health status)49 allowing the estimation of quality-adjusted life-years (QALYs; health states given an overall social preference value or ‘utility’) for ACC-SI 50 51

The ACC electronic database : Provides information about SI not available from the POIS interviews in isolation, including (1) date of ACC-SI event, (2) ACC-SI nature of injury grouping, (3) anatomical site, (4) diagnosis codes to derive ACC-SI severity, standard errors (5) mechanism and location of SI event, (6) whether ACC-SIs were entitlement or treatment-only claims, (7) whether ACC-SIs resulted in ACC earnings-related compensation payments (and dates) and (8) health and rehabilitation services provided and associated costs.

The NMDS : Provides information about ACC-SI resulting in hospitalisation (and hospital treatment exceeding 3 hours), including the length of stay, procedure codes and diagnoses at discharge.

…”
Section: Design and Methodsmentioning
confidence: 99%
“…For many measures, participants were asked about their status before their sentinel injury, as well as at 3, 5, 12 and 24 months afterwards,13 allowing adjustment for pre-sentinel injury status. Validated outcome measures include WHO Disability Assessment Schedule (WHODAS; disability),47 Kessler-6 (psychological distress)48 and the EQ-5D (general health status)49 allowing the estimation of quality-adjusted life-years (QALYs; health states given an overall social preference value or ‘utility’) for ACC-SI 50 51…”
Section: Design and Methodsmentioning
confidence: 99%
“…Follow-up rates were higher than, or comparable with, those of studies that used similar recruitment methods. [38][39][40][41][42] Limitations include a potential selection bias: 30% of eligible patients who were approached took part, and participants and non-participants may have differed in terms of their likelihood of returning to work. It was also not possible to explore the impact of injuries on changes to jobs and hours of work; further work is required to address this.…”
Section: Strengths and Limitationsmentioning
confidence: 99%